Developing PIAUD Students' Competence as Prospective Teachers in Designing Arabic Learning for Young Children: A Conceptual Framework for STAI Kuningan - Mubarok Fatahillah; Husnul Hafidhoh; Betsi Siti Nurhidayah (Jurnal Pendidikan Indonesia, 2026)
Prospective teachers in Islamic Early Childhood Education (PIAUD) require integrated competencies to design Arabic learning that is linguistically accurate, developmentally appropriate, engaging, inclusive, and pedagogically meaningful. However, existing teacher preparation frequently separates Arabic language knowledge, early childhood pedagogy, learning media, and assessment, resulting in fragmented professional competence. This study aims to develop an evidence-informed competency framework to guide the preparation of PIAUD students at STAI Kuningan in designing Arabic learning for young children. The study employed a structured narrative review with an integrative conceptual synthesis by examining 18 selected scholarly and policy sources related to pedagogical content knowledge, early childhood education, Arabic language teaching, digital competence, learning media, and preservice teacher education. Thematic coding and conceptual comparison were used to identify recurring competency components and integrate them into a coherent framework. The findings generated six interrelated competency domains: child-development alignment, Arabic linguistic and content accuracy, coherence among objectives, activities, and assessment, play-based interaction and scaffolding, purposeful and safe media integration, and assessment, differentiation, and reflective improvement. The review also identified a recurring preparation gap in which confidence in using digital tools does not necessarily reflect integrated teaching competence. The proposed framework provides a practical foundation for curriculum redesign, authentic assessment, portfolio development, and future empirical validation to strengthen the preparation of prospective PIAUD teachers.